2021
DOI: 10.1097/prs.0000000000007523
|View full text |Cite
|
Sign up to set email alerts
|

Local Triamcinolone Treatment Affects Inflammatory Response in Seroma Exudate of Abdominoplasty Patients: A Randomized Controlled Trial

Abstract: Background: As the leading complication of abdominoplasty, seroma formation might represent an inflammatory process in response to surgical trauma. This prospective randomized trial investigated whether local administration of the antiinflammatory agent triamcinolone could prevent seroma accumulation. Methods: Weekly and cumulative seroma volumes were compared between the study groups A, B, and C over a 4-week follow-up (group A, with drain, without tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…It was observed that local administration of 80mg of triamcinolone reduced postabdominoplasty formation of seroma markedly with the decrease in levels of IL-6 in seroma fluid. The suppression of inflammatory markers corresponded clinically with a reduction in seroma accumulation 22 . Likewise, the employment of injection triamcinolone in breast reconstruction surgery illustrated that 55% patients did not have formation of seroma.…”
Section: Discussionmentioning
confidence: 75%
“…It was observed that local administration of 80mg of triamcinolone reduced postabdominoplasty formation of seroma markedly with the decrease in levels of IL-6 in seroma fluid. The suppression of inflammatory markers corresponded clinically with a reduction in seroma accumulation 22 . Likewise, the employment of injection triamcinolone in breast reconstruction surgery illustrated that 55% patients did not have formation of seroma.…”
Section: Discussionmentioning
confidence: 75%
“…Topical administration of triamcinolone has been proposed as an effective treatment for seroma after latissimus dorsi flap harvesting and abdominoplasty. [7,8] Triamcinolone may prevent seroma from oozing into the dead space due to decreased vascular permeability and has an anti-inflammatory action that suppresses arachidonic acid synthesis, which plays a key role in the production of prostaglandins and leukotrienes. [10] In the case presented here, the exudate from the chronic granulation might have immersed the skin wound due to flap harvesting because of the absence of adhesion between the flap and peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Local injection of triamcinolone has been reported to reduce pericardial fluid, ascites, and subcutaneous seroma formation after latissimus dorsi flap harvesting and abdominoplasty. [4][5][6][7][8] This report describes a case in which triamcinolone was injected locally, effectively decreasing exudate from the retroperitoneum that had been exposed for a prolonged period, thereby leading to wound closure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies have tried to identify possible risk factors contributing to seroma formation, as well as strategies to minimize these risks. Preventive measures and surgical strategies have been proposed to reduce the incidence of seromas—especially after breast surgery, flap harvesting, abdominoplasty, and lymph node dissections—and include quilting and progressive tension sutures [ 1 ], sclerosing or adhesive substances, the application of triamcinolone or talc [ 2 ], as well as compression and immobilization [ 3 , 4 , 5 , 6 , 7 ]. Other studies have proposed comorbidities, such as increased BMI and hypertension, as possible risk factors in the development of seromas [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%